Early gastric stump cancer following distal gastrectomy. Issue 3 (1st September 1998) - Kaneko, K; Kondo, H; Saito, D; Shirao, K; Yamaguchi, H; Yokota, T; Yamao, G; Sano, T; Sasako, M; Yoshida, S
Abstract : Background —Gastric stump cancer (GSC) is usually diagnosed at an advanced stage, and consequently the prognosis is poor. Aims —To investigate the clinicopathological characteristics of GSC at an early stage to assist in its identification, and thereby improve its prognosis. Methods —Forty three patients with resected early GSC were compared with 156 patients with resected primary early cancer in the upper third of the stomach. Results —Sixty five per cent (28/43) of the early GSC patients showed the elevated type endoscopically, although the frequency of the depressed type in GSC has tended to increase in the past five years. This occurred in less than 26% (40/156) of the primary early cancers. Half of the early GSCs were located on the lesser curvature (47%), and revealed differentiated adenocarcinoma (81%) histologically. The male:female ratio of early GSC cases was about 6:1, which was much higher than that in patients with primary early cancer. The five year survival rates of patients with early GSCs and early primary cancers were 84% and 95%, respectively. GSC had a favourable prognosis, if it was detected at an early stage. Conclusion —To detect early GSC, our results suggest that special attention should be given to elevated as well as depressed lesions on the lesser curvature of the stomach, particularly in men, during endoscopic examinations.